Novel Optineurin Frameshift Insertion in a Family With Frontotemporal Dementia and Parkinsonism Without Amyotrophic Lateral Sclerosis - Dominguez, Jacqueline; Yu, Jeryl Tan; Tan, Yi Jayne; Ng, Arlene; De Guzman, Ma Fe; Natividad, Boots; Daroy, Ma Luisa; Cano, Jemellee; Yu, Justine; Lian, Michelle M.; Zeng, Li; Lim, Weng Khong; et al. (Frontiers in Neurology, 2021)
Frontotemporal Dementia (FTD) is a common cause of Young Onset Dementia and has diverse clinical manifestations involving behavior, executive function, language and motor function, including parkinsonism. Up to 50% of FTD patients report a positive family history, supporting a strong genetic basis, particularly in cases with both FTD and amyotrophic lateral sclerosis (FTD-ALS). Mutations in three genes are associated with the majority of familial FTD (fFTD) cases - microtubule associated protein tau gene (MAPT), granulin precursor (GRN), and hexanucleotide repeat expansions in chromosome 9 open reading frame 72- SMCR8 complex subunit (C9orf72)while mutations in other genes such as optineurin (OPTN) have rarely been reported. Mutations in OPTN have been reported mostly in familial and sporadic cases of ALS, or in rare cases of FTD-ALS, but not in association with pure or predominant FTD and/or parkinsonian phenotype. Here, we report for the first time, a family from the Philippines with four members harboring a novel frameshift insertion at OPTN (Chr 10:13166090 G>GA) p.Lys328GluTer11, three of whom presented with FTD-related phenotypes. Additionally, one sibling heterozygous for the frameshift insertion had a predominantly parkinsonian phenotype resembling corticobasal syndrome, but it remains to be determined if this phenotype is related to the frameshift insertion. Notably, none of the affected members showed any evidence of motor neuron disease or ALS at the time of writing, both clinically and on electrophysiological testing, expanding the phenotypic spectrum of OPTN mutations. Close follow-up of mutation carriers for the development of new clinical features and wider investigation of additional family members with further genetic analyses will be conducted to investigate the possibility of other genetic modifiers in this family which could explain phenotypic heterogeneity.